Comparison Between Conventional Intervention and Non-immersive Virtual Reality in the Rehabilitation of Individuals in an Inpatient Unit for the Treatment of COVID-19: A Study Protocol for a Randomized Controlled Crossover Trial - Silva, Talita Dias da; Oliveira, Patricia Mattos de; Dionizio, Josiane Borges; Santana, Andreia Paiva de; Bahadori, Shayan; Dias, Eduardo Dati; Ribeiro, Cinthia Mucci; Gomes, Renata de Andrade; Ferreira, Marcelo; Ferreira, Celso; Moraes, Íbis Ariana Peña de; Silva, Deise Mara Mota; et al. (Frontiers in Psychology, 2021)
Background: The new human coronavirus that leads to COVID-19 has spread rapidly around the world and has a high degree of lethality. In more severe cases, patients remain hospitalized for several days under treatment of the health team. Thus, it is important to develop and use technologies with the aim to strengthen conventional therapy by encouraging movement, physical activity and improving cardiorespiratory fitness for patients. In this sense, therapies for exposure to virtual reality are promising and has been shown to be an adequate and equivalent alternative to conventional exercise programs. Aim: this is a study protocol with the aims to compare the conventional physical therapy intervention and the use of a non-immersive virtual reality software during COVID-19 hospitalization. Methods: Fifty patients hospitalized with confirmed diagnosis of COVID-19 will be divided in two groups under physiotherapy treatment using conventional or virtual reality intervention. Group A: participants with COVID-19 who will start the first day of the protocol with virtual reality tasks in the morning and then in the second period, in the afternoon, will perform the conventional exercises (n = 25). Group B: participants with COVID-19 who will start the first day with conventional exercises in the morning and in the second period, in the afternoon, will perform activity with virtual reality (n = 25). All participants will be evaluated with different motor and physiologic scales before and after the treatment to measure improvements. Conclusion: Considering the importance of benefits from physical activity during hospitalization, a virtual reality software shows promise as a potential mechanism for improving physical activity. The results of this study may provide new insights into hospitalization rehabilitation.